Therapeutic efficacy of selective intraarterial chemoradiotherapy with docetaxel and nedaplatin for human papilloma virus-negative oropharyngeal cancer. Issue 3 (June 2022) - Heianna, Joichi; Makino, Wataru; Hirakawa, Hitoshi; Agena, Shinya; Tomita, Hayato; Ariga, Takuro; Ishikawa, Kazuki; Takehara, Shota; Kusada, Takeaki; Maemoto, Hitoshi; Maeda, Hiroyuki; Murayama, Sadayuki
Abstract: Objective: Human papilloma virus-negative oropharyngeal cancer has not achieved satisfactory outcomes compared with those of human papilloma virus-positive oropharyngeal cancer. This study evaluated the therapeutic efficacy of selective intraarterial chemoradiotherapy with the docetaxel and nedaplatin regimen for human papilloma virus-negative oropharyngeal cancer. Methods: Twenty-two consecutive patients with human papilloma virus-negative oropharyngeal cancer who had undergone selective intraarterial chemoradiotherapy were retrospectively analyzed. The primary tumor and whole neck were irradiated (50 Gy). Subsequently, the primary site and metastatic lymph nodes were boosted by 20 Gy. The intraarterial chemotherapy regimen comprised a combination of nedaplatin (80 mg/m 2 ) and docetaxel (60 mg/m 2 ), which was initially administered at the start of radiotherapy and was given every 4 weeks for three sessions. Each intraarterial dose of an anticancer agent was determined according to the percentage of the tumor volume supplied by the target artery to the total tumor volume, which was intraoperatively measured via cone-beam computed tomography. The outcome measures were locoregional control, disease-free survival, and overall survival rates and adverse events. Statistical analyses were performed using the Kaplan–Meier method. Results: The median follow-up period was 59 (range, 15–103) months. The T stage was T1/T2 in 5 patients (23%), T3 in 5 patients (23%), and T4 in 12 patients (54%). Cervical lymph node metastasis was staged as ≥N2c in 7 (32%) patients. Complete response was achieved in all patients at the first imaging examination after intraarterial chemoradiotherapy. The 5-year locoregional control, disease-free survival, and overall survival rates were 96% (95% confidence interval, 0.72–0.99), 91% (95% confidence interval, 0.68–0.98), and 100% (95% confidence interval, not available), respectively. Regarding serious acute adverse events, grade 4 laryngeal edema and leukopenia were observed in 1 (5%) and 11 patients (50%), respectively. No other serious acute adverse events were observed. Conclusion: Selective intraarterial chemoradiotherapy with docetaxel and nedaplatin has the potential to achieve favorable locoregional control, disease-free survival, and overall survival rates in human papilloma virus-negative oropharyngeal cancer.